Effects of puberty on cystic fibrosis related pulmonary exacerbations in women versus men. Issue 1 (4th March 2013) - Sutton, Shelby; Rosenbluth, Daniel; Raghavan, Deepa; Zheng, Jie; Jain, Raksha
Abstract Background Epidemiologic data from studies of airway diseases, such as asthma, chronic obstructive pulmonary disease, and cystic fibrosis indicate a gender disparity where women have worse outcomes. The explanation for this is largely unknown. We hypothesize that female sex hormones play a role in this gender disparity, predisposing women to more exacerbations and decreased lung function post‐puberty. Objective In Cystic Fibrosis, to determine if puberty marks a point of increasing exacerbations and decreasing lung function in women relative to men. Methods Using the United States Cystic Fibrosis Foundation Patient Registry, we used linear regression to compare lung function and rate of pulmonary exacerbations in men versus women before and after puberty. Results Of 5, 137 subjects who met inclusion criteria, 2, 689 were male and 2, 448 were female. Average age of puberty was found to be 13.2 ± 2.2 years in men and 11.2 ± 2.0 years of age in women. Percent predicted FEV1 pre‐ and post‐puberty were no different between males versus females (P = 0.44 pre‐puberty and P = 0.16 post‐puberty). In contrast, women had a significantly higher rate of pulmonary exacerbations post‐puberty than men (1.17 ± 1.35 exacerbations per year in women versus 0.95 ± 1.27 in men; P < 0.001) despite controlling for morphometrics, co‐morbidities, and microbiologic variables. Conclusion After puberty, the rate of pulmonary exacerbations increased in adolescent women relative to men with cystic fibrosis, supporting a role for sex hormones in the disease process. Further understanding of the mechanisms that modulate sex hormone receptors in airway disease may serve as future targets for therapy. Pediatr Pulmonol. 2014; 49:28–35. © 2013 Wiley Periodicals, Inc.